Construction of Virtual Neuron and Consolidation of Sleep and Memory Process– A Molecular Docking and Biomathematical Approach - Bin, Zhao; Jinming, Cao; Kuiyun, Huang; Xia, Jiang; Jingfeng, Tang (Journal of Model Based Research, 2019)
This methods paper combines molecular docking and biomathematical modeling to construct a virtual neuron framework for studying sleep‑related memory consolidation. It outlines model components and validation approach.
Keywords: Virtual Neuron; two-stage model; SWS sleep; REM sleep; memory consolidation; sleep deprivation